Teste de eficiência da magic formula de value investing para o mercado brasileiro de ações - Milane, Leonardo Pelae (2016)
The main purpose of this work is to back-test the Magic Formula in the IBX- 100 index, in order to gather evidence of effectiveness of the respective methodology in the selection of the best stocks and portfolios that beat the IBX-100 in the long run. The Magic Formula was developed by Joel Greenblatt and consists in a methodology for stock picking that creates portfolios of stocks with high ROICs and high Earnings Yield, following the Value Investing philosophy. Many portfolios were created in the period between January 2000 and June 2015 combining different number of stocks per portfolio and different holding periods. Some portfolios did beat the market index, while some did not. Portfolios with a higher number of stocks and longer holding periods seem to perform better than portfolio with fewer stocks and shorter holding periods. The portfolio with 10 stocks, holding period of 1 year, showed the highest CAGR among all portfolios (17,77%), surpassing the IBX-100 CAGR of 13,17% in the same period, even risk-adjusting. Regardless the holding period and the number of stocks, all portfolios presented lower systematic risk than the IBX-100 index (all betas were significant and lower than 1). On the other hand, all alphas were low, rarely significant, suggesting that the active portfolio management that follows the Magic Formula criteria did not add substantial higher returns when compared to market returns.